Design and experiments of multi-stage coil gun system - Su-Jeong Lee (Journal of Vibroengineering, 2016)
An electromagnetic launcher (EML) is a device used to propel and accelerate a projectile by converting electrical energy into kinetic energy. A coil gun, which is a type of EML, can propel a projectile without any mechanical friction so that there is no theoretical limit to the velocity. A multi-stage system is a way to raise the effectiveness of the coil gun. It accelerates the projectile by controlling the relations between each stage of the solenoid and projectile. Since a multi-stage system controls the time needed to apply electric current to the coil depending on the position of the projectile, the switching time is extremely important. We performed a finite element analysis using MAXWELL to determine the extent to which the velocity of a multi-stage coil gun improved compared to a single-stage coil gun. In addition, we verified the two-stage performance through timing control by designing and producing a two-stage coil gun based on our research results for a single-stage coil gun. The velocity was increased by 34 % compared to the single-stage coil gun, and the error compared to the analysis result was 16.4 %.